Perbandingan Struktur Tubuh dan Kemampuan Atletik SMAN 9 Kab. Bone Dengan Smk YAPIP Kab. Gowa - Andi Khemal Akbar (Jendela Olahraga, 2020)
This study aims to investigate the difference between the students at Senior Highr School of Bone distric and Senior High School YAPIP Gowa distric in term of physical structure and to describe the difference between the students at both school in term of athletic skill. This research applied experimental design. The population of the research were all of the students at Senior Highr School 9 Bone distric and Senior Highr School YAPIP Gowa distric, meanwhile the sample were 40 male students of each school. The researcher applied random sampling technique. It shows that there is a significant difference between the physical structure of the students at both schools. The result of t-test shows that there is a significant difference in physical structure between the students of Senior Highr School 9 Bone distric and Senior Highr School YAPIP Gowa distric. In this case, the physical structure of the students at Senior Highr School 9 Bone distric is better that the students at Senior Highr School YAPIP Gowa distric. Besides, there is a significant difference regarding athletic skill. In this case, the athletic skill of the students at Senior Highr School 9 Bone distric is better that the students at Senior High School YAPIP of Gowa distric.Keywords: Physical Structure, Athletic Skill, SMAN 9 Kab. Bone, SMA YAPIP Kab. GowaAbstrakPenelitian ini bertujuan untuk mengetahui ada tidaknya perbedaan struktur tubuh antara siswa SMAN 9 Kab. Bone dengan siswa SMA YAPIP Kab. Gowa, dan menjelaskan perbedaan kemampuan atletik antara siswa di kedua sekolah. Metode penelitian ini adalah jenis penelitian eksperimen. Populasi pada penelitian ini adalah seluruh siswa SMAN 9 Kab Bone dan seluruh siswa SMA YAPIP Kab. Gowa. Sedangkan sampel yang digunakan adalah 40 siswa dari masing-masing sekolah. Teknik pengambilan sampel dilakukan teknik random sampeling (acak). Ada perbedaan yang signifikan antara struktur tubuh siswa di kedua sekolah. Hasil rangkuman uji – t menunjukkan bahwa ada perbedaan yang signifikan antara struktur tubuh siswa di kedua sekolah. Dalam hal ini struktur tubuh siswa SMAN 9 Kab. Bone lebih baik dibandingkan dengan struktur tubuh siswa SMA YAPIP Kab. Gowa. Selain itu, ada perbedaan yang signifikan antara kemampuan atletik siswa SMAN 9 Kab. Bone dengan siswa SMA YAPIP Kab. Gowa. Dalam hal ini kemampuan atletik siswa SMAN 9 Kab. Bone lebih baik dibandingkan dengan kemampuan atletik siswa SMA YAPIP Kab. Gowa.Kata kunci: Struktur Tubuh, Kemampuan Atletik, SMAN 9 Kab. Bone, SMA YAPIP Kab. Gowa